The Stoichiometric Interaction of the Hsp90-Sgt1-Rar1 Complex by CD and SRCD Spectroscopy - Siligardi, Giuliano; Zhang, Minghao; Prodromou, Chrisostomos (Frontiers in Molecular Biosciences, 2018)
While the molecular details by which Hsp90 interacts with Sgt1 and Rar1 were previously described the exact stoichiometric complex that is formed remains elusive. Several possibilities remain that include two asymmetric complexes, Sgt12-Hsp902-Rar12 (two molecules of Sgt1 and Rar1 and one Hsp90 dimer) or Sgt12-Hsp902-Rar11 (with a single Rar1 molecule) and an asymmetric complex (Sgt11-Hsp902-Rar11). The exact stoichiometry of such a complex may have a direct impact on NLR (nucleotide-binding domain and leucine-rich repeat) protein oligomerization and thus ultimately on the mechanism by which NLRs are activated. CD spectroscopy was successfully used to determine the stoichiometry of a ternary protein complex among Hsp90, Sgt1 and Rar1 in the presence of excess ADP. The results indicated that a symmetric Sgt12-Hsp902-Rar11 complex was formed that could allow two NLR molecules to simultaneously bind. The stoichiometry of this complex has implications on, and might promote, the dimerization of NLR proteins following their activation.